Financial Literacy, Income, Lifestyle, and Consumptive Behaviour among Student Workers - Yohanes De Poseng; Rolland E. Fanggidae; Nikson Tameno (Studi Akuntansi dan Bisnis Indonesia, 2026)
Purpose: This study examines the effects of financial literacy, income, and lifestyle on the consumptive behavior of student workers partnered with online transportation companies in Kupang, Indonesia. Methodology: This study used a quantitative survey of 100 student workers. Data were collected using questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics 27. Results: Financial literacy had a significant negative effect on consumption behavior, whereas lifestyle had a significant positive effect. Income had no significant effect on the results. Simultaneously, the three variables significantly influenced consumption behavior, with an R² value of 0.336. Conclusions: Financial literacy and lifestyle are key determinants of the consumptive behavior of student workers, whereas income does not directly influence consumptive tendencies. Limitations: This study is limited to student workers in Kupang City and used a cross-sectional, self-reported survey design. Contribution: This study contributes to the behavioral finance literature by highlighting the importance of financial literacy and lifestyle control in reducing excessive consumption among gig economy student workers.